Hadith #4189 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sufyan bin 'Uqba al-Swa'iy سفيان بن عقبة السوائي الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wa'il bin Hujr al-Kundi al-Hadrami (Sunan Abi Dawud)
When I parted the hair of the Messenger of Allah (ﷺ) I made a parting from the crow of his head and let his forelock hang between his eyes.
Grade: Hasan